Bull riding: Analysis and application of a specific strength and conditioning program - Barrett, M. R.; Butterwick, D. J.; Smith, D. J. (Strength and Conditioning Journal, 2006)
Because bull riding is one of the most dangerous of extreme sports, it is very important to make efforts to improve the safety and the performance of its participants. A strength and general physical fitness program will better prepare riders for the demands of bull riding. The purpose of this paper is to describe the physiological demands of bull riding and to introduce a periodized strength and general fitness model.